Covering Islam in Western Media: From Islamic to Islamophobic Discourses - Bouchaib Benzehaf (Yayasan Visi Intan Permata, 2017)
A fundamental role allocated to the media is the shaping of public opinion about topical issues, thus making the act of obtaining accurate and verified information a major challenge. In this context, Said (1997) argues that coverage of Islam by the media has always been lacking in subjectivity, and Arabs/Muslims have at best been obscured and at worst “othered” and demonized rather than revealed by the media. The 9/11 attacks have re-triggered an explosion of media coverage of Islam and Muslims with the terms